Interim analysis of a prospective observational multicenter registry study of patients with chronic heart failure in the Russian Federation "PRIORITET-CHF": initial characteristics and treatment of the first included patients - E. V. Shlyakhto; Yu. N. Belenkov; S. A. Boytsov; S. V. Villevalde; A. S. Galyavich; N. G. Glezer; N. E. Zvartau; Zh. D. Kobalava; Yu. M. Lopatin; V. Yu. Mareev; S. N. Tereshchenko; I. V. Fomin; et al. (Российский кардиологический журнал)
Aim. To describe demographic and clinical laboratory characteristics, concomitant diseases and drug therapy of outpatients with heart failure (HF) in the Russian Federation.Material and methods. An interim analysis of a prospective observational multicenter registry study of patients with chronic heart failure in the Russian Federation ("PRIORITET-CHF") was performed. The study included outpatients with HF followed by a general practitioner or cardiologist.Results. Data from 6255 patients were analyzed (31,3% of the study sample; median age, 65 years; men, 65%). HF with reduced ejection fraction (HFrEF) was diagnosed in 42,4%, HF with preserved EF — in 31,9%. In addition, 57,4% of patients were characterized by NYHA class II HF. The most common causes of HF were hypertension, coronary artery disease, and atrial fibrillation or flutter. Of the concomitant diseases, doctors most often reported chronic kidney disease (CKD) (43,2%), obesity (37,8%) and diabetes (26,7%) in HF.Conclusion. In the Russian Federation, among outpatients with HF, there was domination of men, HFrEF phenotype, NYHA class II. The relatively young mean age and frequent associations of HF with cardiovascular risk factors and diseases underscore the importance of timely prevention initiatives. The identified high proportion of patients with CKD requires special attention and separate analysis. Despite the relatively high prescription rate of certain classes of diseasemodifying therapy for HF, the prescription of optimal quadruple therapy and electrophysiological treatments for HFrEF is insufficient.